71.1k views
0 votes
Help please and thank youuu

Help please and thank youuu-example-1
User Raad
by
6.7k points

1 Answer

3 votes

Answer:


a_1=-4\\d=7\\x=3\\y=10\\z=17

Explanation:

First term is the first term in the sequence. The sequence formula is given as


a_n=-4+7(n-1), where n is the
n^(th) term. The first term,
a_1, can be directly lifted from the expression.


a_1=-4

The common difference can be obtained by as
(n_2)/(n_1) or lifted from the expression.


d=7

Substitute for n in the expression to obtain the 2nd, 3rd and 4th terms (x,y,z) as:-


a_2(x)=-4+7(2-1)=3\\a_3(x)=-4+7(3-1)=10\\a_4(x)=-4+7(4-1)=17\\

User BlueIceDJ
by
5.5k points